(untitled) (Journal of the College of Basic Education, 2022)
The subject of the research included (the scientific movement in Homs during the reign of the Ayyubids for the period 563-662 AH / 1168-1263 AD).It is the period of the rule of the Ayyubids of the city of Homs since Asad al-Din Shirkuh I, the uncle of Salah al-Din al-Ayyubi, took over the rule of Homs until the death of Sultan Abu al-Fath Muzaffar al-Din Musa, who was the last of the Ayyubids to rule Homs. The reason for its name, which historians and geographers have said about it, touched on its historical importance, and that it is one of the ancient cities that the Arabs moved to and inhabited before the advent of Islam because of its distinguished location, which gave it economic and political importance, which made the Romans and others throughout the ages seek to control it, and it ended up being liberated by the Arab Muslims and became within the state Islamic Arabic.